Noninvasive respiratory support for acute respiratory failure—high flow nasal cannula oxygen or non-invasive ventilation? - Curley, Gerard F.; Laffy, John G.; Zhang, Haibo; Slutsky, Arthur S. (Journal of Thoracic Disease; Vol 7, No 7 (July 30, 2015): Journal of Thoracic Disease, 2015)
For patients with acute respiratory failure there may be advantages to the avoidance of invasive mechanical ventilation, i.e., ventilation via endotracheal intubation. Indeed, soon after the introduction of invasive mechanical ventilation many complications of positive pressure ventilation were identified (1,2). Some are directly related to the intubation procedure, such as cardiac arrest following endotracheal intubation, and laryngeal or tracheal injury leading to long-term sequelae. Others are related to the fact that the endotracheal tube adversely affects pulmonary host defenses (e.g., cough, mucociliary transport) setting the stage for ventilator-associated pneumonia, that carries its own risk of morbidity and mortality (3). Invasive mechanical ventilation generally requires sedation, which itself is often a cause of prolonged weaning and prolonged mechanical ventilation.